Interseason variability in isokinetic strength and poor correlation with nordic hamstring eccentric strength in football players - van Dyk, N.; Witvrouw, E.; Bahr, R. (Scandinavian Journal of Medicine & Science in Sports, 2018)
Introduction: In elite sport, the use of strength testing to establish muscle function and performance is common. Traditionally, isokinetic strength tests have been used, measuring torque during concentric and eccentric muscle action. A device that measures eccentric hamstring muscle strength while performing the Nordic hamstring exercise is now also frequently used.